Research progress of siloxane removal from biogas - Ruiling, Gao; Shikun, Cheng; Zifu, Li (International Journal of Agricultural and Biological Engineering, 2017)
Siloxanes in biogas are detrimental to engine, turbine, fuel cell, etc., thus it is necessary to remove siloxanes from biogas before biogas high-value utilization. At present, there are few domestic researches and related reports in view of siloxanes removal from biogas. This paper introduces the property of siloxanes as well as sampling and analysis method, and then presents the research progress of siloxanes removal from biogas. Three commercial technologies overseas are adsorption, absorption and cryogenic condensation. Among them, adsorption on activated carbon is the most widely used method. Other technologies, such as biological removal, catalytic processes, membranes, source controlling, etc. are under exploration and development. At last, this paper summarizes the advantages and disadvantages of siloxanes removal technologies as well as the applicability and analyzes the future research trend and emphasis. This paper could provide a reference in the field of biogas high-value utilization.Keywords: biogas, purification, siloxane removal, activated carbon adsorption, physical and chemical absorption, biological removalDOI: 10.3965/j.ijabe.20171001.3043Citation: Gao R L, Cheng S K, Li Z F. Research progress of siloxane removal from biogas. Int J Agric & Biol Eng, 2017; 10(1): 30–39.